MODEL COMPONENTS OF MANGROVE RESOURCES MANAGEMENT BASED ON BLUE ECONOMY CONCEPT - Endang Bidayani; Soemarno Soemarno; Nuddin Harahab; Rudianto Rudianto (Faculty of Fisheries and Marine Science, Brawijaya University, 2016)
This study was aimed at analyzing variables affecting mangrove resource conservation based on blue economy concept. The model component analysis applied Spearman Rank Correlation test. Result showed that Z-calc.was bigger than Z-tab. (1.64) at 95% confidence level, and therefore, Ho was rejected. This study concluded that resource efficiency, without wastes, social awareness, cyclic system of production, innovation and adaptation, and institution were blue economy concept-based variables. In this case, institutional management of good governance is highly needed. Nevertheless, this study has still focused on limited issues, and therefore, more variables should be added in future studies in relation with their impacts on the blue economy management. Keywords: blue economy, management, mangrove, conservation